2023
DOI: 10.1007/s13278-022-01021-4
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making approaches in the antagonistic digital communication of the online communities users

Abstract: The information space is an effective hybrid warfare tool on the web. This study investigated the decision-making process in the antagonistic digital communication of internet services users. Implementation of the proposed methods in this study minimized the negative impact of the spread of destructive content and actions of unfair competitors in the ecosystem of social internet services. The innovativeness of the suggested methods is the ability to make real-time decisions in a situation of antagonistic behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Lee et al [10] found that the use of digital technology by older adults reduced the symptoms of depression caused by fewer social interactions, and they emphasized that enhanced digital access might have improved the mental health of older adults during the pandemic. In critical situations, people often rely on online services to obtain medical-related information and answers [49]. Therefore, the application of communication technology can affect every aspect of the daily life of the elderly.…”
Section: The Relationship Between Ict Use and Perceived Life Satisfac...mentioning
confidence: 99%
“…Lee et al [10] found that the use of digital technology by older adults reduced the symptoms of depression caused by fewer social interactions, and they emphasized that enhanced digital access might have improved the mental health of older adults during the pandemic. In critical situations, people often rely on online services to obtain medical-related information and answers [49]. Therefore, the application of communication technology can affect every aspect of the daily life of the elderly.…”
Section: The Relationship Between Ict Use and Perceived Life Satisfac...mentioning
confidence: 99%
“…This can be due to the fact that decision-makers may plan actions that will take place in the future or because their decisions are not always based on actual knowledge or absolute principles, but on assumptions, perceptions, opinions, and personal values or beliefs. Fedushko et al ( 2023 ) suggest that strategic decision-making, based on OSN, involves understanding the interconnected decisions and their impact on network users to gain an advantage. On the other hand, Antunes and Costa ( 2011 ) argue that decision-making support processes should incorporate rational aids instead of mere “gut feelings”, thus enhancing the possibility of making better decisions.…”
Section: Social Network Analysis and Decision-making Support For Airl...mentioning
confidence: 99%
“…Digitization services are an effective means of influencing all policies and practices (Doran et al, 2023). Therefore, it is recommended that the appearance of the web always be oriented towards creative formulation and innovation (Fedushko et al, 2023). Churches also need online services.…”
Section: "Air Hidup" Therapy As An Online Service For Church Congrega...mentioning
confidence: 99%